Associations of physical activity and cardiorespiratory fitness with cognitive function, self-control, and resilience in young people with attention deficit hyperactivity disorder - Elise Sibbick; Ruth Boat; Mustafa Sarkar; Julie P. Johnston; Maddie Groom; Ryan A. Williams; Karah J. Dring; Feng-Hua Sun; Simon B. Cooper (Advanced Exercise and Health Science)
The aim of the present study was to investigate if physical activity and cardiorespiratory fitness influence cognition, self-control, and resilience in young people with ADHD. Fifty-four children with ADHD (12.8 ± 1.4 y) completed questionnaires to assess self-control and resilience, wore an accelerometer for 7 d to assess free-living physical activity, and completed a battery of cognitive function tasks and a multi-stage fitness test (cardiorespiratory fitness). Positive associations were found between cardiorespiratory fitness and attention, measured via performance on the simple Stroop task (r(52) = −0.386, p = 0.004) and the congruent Flanker task (r(52) = −0.302, p = 0.026), and inhibitory control, measured via performance on the incongruent level of the Flanker task (r(52) = −0.348, p = 0.010). Furthermore, a higher proportion of active time spent in high-intensity activities (r(37) = 0.370, p = 0.021) were associated with higher self-control. No associations were found between physical activity or cardiorespiratory fitness and resilience (all p > 0.05). These findings demonstrate the importance of physical activity and cardiorespiratory fitness for cognition and self-control in young people with ADHD.